Wireless Internet handbook : technologies, standards, and applications - Furht, Borivoje; Ilyas, Mohammad, 1953- (Internet and communications., 2003)
Wireless local access to the mobile Internet, user mobility in IP networks, multimedia streaming over wireless Internet, quality of service issues, location management techniques and clustering architectures, wireless Internet security issues, Bluetooth, CDMA, TDMA, Wireless Application Protocol, 802.11x, different mobile and wireless Internet services, wireless Internet enterprise applications, mobile multimedia and graphics applications, mobile video telephony, wireless video surveillance, wireless applications in medicine.